Análisis de la situación actual, la falta de protección a los derechos por parte de las Juntas Cantonales de Protección de Derechos - Aguirre Guachisaca, Jorge Javier (2024)
This curricular integration work entitled "The Current Situation of the Cantonal Boards for the Protection of Rights" focuses on analyzing the situation currently faced by the Cantonal Boards for the Protection of Rights, addressing issues such as the lack of infrastructure, the absence of technical personnel specialized and insufficient financial resources. These deficiencies affect these bodies in charge of safeguarding, defending and guaranteeing rights, which is a relevant problem in society and entails negative consequences for people who experience violations of their personal integrity. The work proposes a possible solution to this social problem. Throughout its development, various issues related to the protection and prevention of different groups are addressed, such as girls, boys and adolescents regulated by the Code for Children and Adolescents, women covered by the Law to Prevent and Eradicate Violence Against Women, and older adults whose rights are supported by the Organic Law of Older Adults. An exhaustive analysis of the problems raised is carried out, including the deficiencies present in the Cantonal Boards for the Protection of Rights, which result from the lack of adequate budget allocation by the Decentralized Autonomous Governments. This lack of resources compromises the rights of the most vulnerable groups. In addition, the study seeks to generate comprehensive solutions that address these problems effectively.